PENERAPAN SISTEM PENGENDALIAN INTERN PEMUNGUTAN PAJAK KENDARAAN BERMOTOR - Azza, Christina; Suhendra, Suhendra (Patria Artha Journal of Accounting dan Financial Reporting, 2024)
This study aims to find out how the internal control system is applied in collecting motorized vehicle taxes to increase regional income at the SAMSAT Kab. Gowa. This research is a quantitative research with a descriptive approach, this research was conducted with data received from the SAMSAT Kab. Gowa in the form of target data and realization of Motor Vehicle Tax revenue at the Gowa Regency SAMSATOffice. The research data carried out is in the form of primary data and secondary data. Where primary data is carried out by interviews and secondary data is in the form of targets and realization of Motor Vehicle Tax revenue. The research results show the level of effectiveness of implementing the internal control system for motor vehicle tax collection at the SAMSAT District office. Gowa has been very effective in increasing regional revenues, although in the risk assessment there are determinations oftargets for Motor Vehicle Tax revenues that go up and down because they have to see potential, KTMDU and previous realization and are still constrained by the E-SAMSAT application connection and taxpayers due to economic factors, and there are still people like brokers. However, from the SAMSAT office Kab. Gowa always follows the government's policy to continue to strive to increase the target of Motor Vehicle Tax revenue because Motor Vehicle Tax has a major impact in increasing regionalrevenue. Motor Vehicle Tax can encourage rapid economic growth in accordance with local government targets.